CONCEPTUAL APPROACH TO ASSESS THE EFFECTIVENESS OF SPATIAL ORIENTATION - U. A. Lukashevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
In the course of the study it was formed a scientifically based concept of an objective assessment of human spatial orientation during performing of complex locomotion. This approach is to perform remote monitoring of cyclic locomotion of step motion «walking on the spot» in terms of the surrounding space. During the test is carried out the spectral evaluation of the acceleration values of the lower extremities in the band from 1 to 10 Hz. It was found that the frequency spectrum reflects the processes of qualitative implementation of spatial orientation. This indicator can be used to objectively assess bio-kinematic stabilize the body in space. The developed technology is innovative and can be used as a rapid method for diagnostic motor and coordinative disorders of various origins.